Comparing living donor and deceased donor liver transplantation: A matched national analysis from 2007 to 2012. Issue 11 (November 2014) - Hoehn, Richard S.; Wilson, Gregory C.; Wima, Koffi; Hohmann, Samuel F.; Midura, Emily F.; Woodle, E. Steve; Abbott, Daniel E.; Singhal, Ashish; Shah, Shimul A.
<x xml:space="preserve">Abstract</x> A complete evaluation of living donor liver transplantation (LDLT) in the United States has been difficult because of the persistent low volume and the lack of adequate comparisons with deceased donor liver transplantation (DDLT). Recent reports have suggested outcomes equivalent to those for DDLT, but these studies did not adjust for differences in recipient selection. From a linkage between the University HealthSystem Consortium and Scientific Registry of Transplant Recipients databases, we identified 14, 282 patients at 62 centers who underwent DDLT from 2007 to 2012 and 715 patients at 35 centers who underwent LDLT during the same period. Then, we performed 1:1 propensity score matching for 708 LDLT recipients based on age, Model for End‐Stage Liver Disease (MELD) score, and pretransplant patient status. The median follow‐up was 2 years. Compared with DDLT recipients, LDLT recipients were more likely to be white (84.5% versus 72.2%) and female (41.1% versus 31.7%), to have lower MELD scores (15 versus 19), and to be classified preoperatively as independent (65.3% versus 46.7%) and not hospitalized (91.3% versus 78.4%). The posttransplant length of stay (LOS), in‐hospital mortality, costs, and survival were similar between the groups, but LDLT recipients were more likely to be readmitted within 30 days (44.9% versus 37.1%, P = 0.001). After matching, the difference in 30‐day readmission rates persisted (45.1% versus 33.8%, P = 0.001), but there were no differences in the LOS, costs, patient survival, or graft survival. This national report shows that LDLT is associated with higher readmission rates in comparison with DDLT, but the results are comparable for other key patient metrics. Liver Transpl 20:1347‐1355, 2014. © 2014 AASLD.